Parameter identification of a yeast batch cell population balance model⁎Funded by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) – Project-ID 395461267. Issue 7 (2021) - Jerono, P.; Schaum, A.; Meurer, T.
Abstract: The parameter identification problem of cell population balance models in a yeast batch process is addressed. The model is described by a partial integro-differential equation coupled with a set of ordinary differential equations. Based on the solution equivalence of the mass balance model and the first moment of the cell population balance model, the identification process is carried out in two steps. The growth related parameters are identified by only taking mass balance based measurements into account. The growth parameters are then utilized to identify the parameters related to cell division in the cell population balance model by means of optimization. The results are verified with an R2 analysis.